2022
DOI: 10.1007/s11240-022-02402-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation and long-term observation of acclimated plants in endangered tree fern Alsophila costularis

Abstract: Alsophila costularis Barker (Cyathea costularis), an endangered tree fern with tree-like erect stem, attracts gardening enthusiasts as a special ornamental plant. In vitro propagation can be advantageous for germplasm conservation and commercial application of A. costularis. Here, we described in vitro propagation of A. costularis via spore culture and green globular bodies (GGBs) system, as well as the long-term observation of acclimated plants regenerated from GGBs. In spore culture, the low concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…The MaxEnt model showed that temperature was the key factor determining the current distribution of A. costularis . Alsophila costularis is difficult to propagate in the wild because its spore germination is impacted by environmental factors, including temperature and moisture (Cheng et al., 1990 ; Pu et al., 2023 ). Ultraviolet radiation can cause injuries to aboveground organs of organisms and limit their distribution (Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MaxEnt model showed that temperature was the key factor determining the current distribution of A. costularis . Alsophila costularis is difficult to propagate in the wild because its spore germination is impacted by environmental factors, including temperature and moisture (Cheng et al., 1990 ; Pu et al., 2023 ). Ultraviolet radiation can cause injuries to aboveground organs of organisms and limit their distribution (Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other ferns of Cyatheaceae, A. costularis has been little studied, especially as regards its ecology. Previous studies have focused on tissue culture (Cheng & Liu, 1992 ), gametophyte development (Wang et al., 2007 ; Xiao et al., 2019 ), DNA extraction (Ying et al., 2009 ), chloroplast genome (Wang et al., 2019 ), and the efficient green globular bodies system (Pu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Rodriguésia 74: e00622023. 2023 (Borelli et al 1990;Avila-Pérez et al 2011;Bharati et al 2013;Suo et al 2015;Alves et al 2019;Pu et al 2023) is related to the broad diversity of nutrients in its composition, which includes vitamins, amino acids and essential macronutrient and micronutrient salts for plant development (Rybczyński & Mikuła 2011). However, depending on the physiology of the cultivated species, metabolic processes can be impaired by this nutrient composition (Murashige & Skoog 1962;Sakuta et al 1987;Grattapaglia & Machado 1998) However, in a study carried out with Dicksonia sellowiana Hook.…”
Section: Discussionmentioning
confidence: 99%
“…Studies aimed at evaluating the influence of nutrient media focus mainly on spore germination and/or sporophyte formation (Avila-Pérez et al 2011;Suo et al 2015;Alves et al 2019;Pu et al 2023), and the development of gametophytes is lacking in discussion. However, the newly germinated spores, with chlorocyte and rhizoid, show fast growth and rapidly develop into gametophytes (Rybczyński & Mikuła 2011), and the gametophytic stage is determinant for the success of fertilization and sporophyte formation.…”
Section: Discussionmentioning
confidence: 99%